2001
DOI: 10.1002/bit.10131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dissolved oxygen (DO) concentration on the glycosylation of recombinant protein produced by the insect cell–baculovirus expression system

Abstract: The effect of dissolved oxygen concentration on human secreted alkaline phosphatase (SEAP) glycosylation by the insect cell-baculovirus expression system was investigated in a well-controlled bioreactor. Oligomannose-type N-linked glycans (i.e., Man2 to Man6 and Man3F) were present in SEAP produced by Spodoptera frusiperda Sf-9 (Sf-9) and Trichoplusia ni BTI-Tn-5B1-4 (Tn-5B1-4) insect cell lines. The relative amounts of the most highly processed glycans (i.e., Man3F and Man2 in the SEAP from Sf-9 and Tn-5B1-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Extreme oxidative or anaerobic conditions, however, appear to interfere with the core-fucosylation of the glycan structures. Similar results were found by Zhang et al (2002), who studied the effect of DO on the glycosylation of secreted alkaline phosphatase (SEAP) produced by insect cells. They found that the fraction of the most highly processed N-glycans (Man3F) were decreased at both 10% and 190% of air saturation compared to 50% or air saturation.…”
Section: Discussionsupporting
confidence: 84%
“…Extreme oxidative or anaerobic conditions, however, appear to interfere with the core-fucosylation of the glycan structures. Similar results were found by Zhang et al (2002), who studied the effect of DO on the glycosylation of secreted alkaline phosphatase (SEAP) produced by insect cells. They found that the fraction of the most highly processed N-glycans (Man3F) were decreased at both 10% and 190% of air saturation compared to 50% or air saturation.…”
Section: Discussionsupporting
confidence: 84%
“…Sialyltransferase activity, sialic acid content, and specific productivity of a recombinant glycoprotein, human follicle stimulating hormone, in CHO cells all increased as DO increased (43). In a well-controlled bioreactor, the glycan processing of the recombinant human secreted alkaline phosphatase in insect cell-baculovirus system was inhibited at both low and high dissolved oxygen concentrations (44). In contrast, another study indicated that the N-glycosylation of an interleukin-2 variant from BHK cells did not changed under low oxygen concentration (45).…”
Section: Process Optimizationmentioning
confidence: 94%
“…The inability of insect cells to perform complex glycosylation is apparently due to the absence or insufficient amounts of the terminal glycosyltransferases that are required to convert N-linked side chains to complex forms (Jarvis et al 1998). Strict control of growth and infection parameters, especially dissolved oxygen also play a major role in glycosylation (Zhang et al 2002). The baculovirus/insect cell system is seen as a promising expression system for obtaining authentic post-translational modification compared to the mammalian and prokaryotic systems.…”
Section: Improving Receptor Expression and Purification For Large Scamentioning
confidence: 99%